Self-reported management among people with rotator cuff related shoulder pain: An observational study. (February 2021) - Smythe, A.; Rathi, S.; Pavlova, N.; Littlewood, C.; Connell, D.; Haines, T.; Malliaras, P.
Abstract: Background: Rotator cuff related shoulder pain is the most common cause of shoulder pain. Whilst guidelines recommend conservative management prior to imaging, injection or surgical management, recent findings suggest that patients experience management contrary to guideline recommendations. Objectives: The aim of this study was to investigate self-reported management among people with rotator cuff related shoulder pain (RCRSP) and their beliefs towards management. Materials and methods: Cross-sectional survey of people with RCRSP recruited when referred for imaging (n = 120). Electronic survey about demographic factors, management people had had (including imaging, injections, surgery, exercise, adjuncts), and beliefs about treatments. The frequency of various treatments was reported (separately for each cohort and traumatic onset) as well as the timing of interventions related to first-line care. Results: Most people had tried exercise (99/120, 82.5%) but only one in five people reported exercise was helpful, and one in six reported it was unhelpful or made their symptoms worse. Approximately a third of the cohort reported not receiving activity modification advice (34.2%, 41/120), those that did received inconsistent information. People with both traumatic (imaging 31/43, 72.1%; injections 13/24, 54.2%, surgery 8/21, 38.1%) and atraumatic onset pain (imaging 43/77, 55.8%; injections 31/51, 60.8%, surgery 4/19, 21.1%) had similarly high rates of intervention prior to trialling conservative management. Patient beliefs in regards to management showed trends towards interventionalist care. Conclusion: Patient reported management of RCRSP is often inconsistent with guideline recommended management. Highlights: Patient opinions on exercise treatment are heterogenous. Many patients have imaging, injection or surgery earlier than recommended. Education received is inconsistent with recommended care. Patient beliefs regarding intervention and diagnosis are varied.